The Study of Exposure to Isophorone and the Risk of Getting Cancer: A Systematic Review and Meta-analysis Protocol - Khavari, Tina; Azizi, Fatemeh; Asadipour, Fatameh; Azari, Mojtaba; Taherian, Mohammad Reza; Karimiyan, Mobina; Soleimani, Yaser; Halimi, Aram; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2023)
Background: This protocol recommends ways to conduct a systematic review and meta-analysis on the association between isophorone exposure and cancer risk. Methods: This study will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligible studies will include observational research examining the association between isophorone exposure and cancer outcomes. General search terms will be used to search databases such as PubMed, Web of Science, and Scopus. Two independent reviewers will screen articles, extract data, and assess study quality and risk of bias. Data synthesis and analysis will include meta-analysis, subgroup analyses, sensitivity analyses, and assessment of publication bias. Results: The systematic review and meta-analysis will provide a comprehensive assessment of the association between isophorone exposure and cancer risk. Data from multiple studies will be pooled to achieve an overall estimate of the association, considering sources of heterogeneity and evaluating the quality of included studies. Publication bias will also be assessed. The findings will contribute to our understanding of the potential health effects of isophorone exposure and inform future research and decision-making. Conclusion: This protocol outlines a systematic and transparent approach to assessing the association between isophorone exposure and the risk of cancer. This study will provide insights into the potential health implications of isophorone exposure, preventive measures, and regulatory decisions. By following established guidelines and employing methodology, this study will provide an evidence-based assessment of the available literature, advancing our understanding of the association between isophorone exposure and cancer risk.